An attempt at a reconciliation of the Sraffian and Kaleckian views on desired utilization - Reiner Franke (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
This paper derives firms' desired rate of utilization from an explicit maximization of a conjectured rate of profit at the micro level. Invoking a strategic complementarity, desired utilization is thus an increasing function of not only the profit share but also the actual utilization. Drawing on recent empirical material and a straightforward functional specification, the model is subsequently numerically calibrated. In particular, this ensures a unique solution for a steady-state position in which the actual and the endogenous desired rates of utilization coincide. On the other hand, it turns out that the anticipated losses of firms by not producing at the desired level are rather small. Hence there may be only weak pressure on them to close a utilization gap in the ordinary way by suitable adjustments in fixed investment. It is indicated that this finding may serve Kaleckian economists as a more rigorous justification for viewing their equilibria as pertaining to the long run, even if they allow actual utilization to deviate persistently from desired utilization.
Keywords: C13; E12; E30; 330; endogenous desired utilization; profit maximization; conjectured profits; strategic complementarities; calibration